2022
DOI: 10.18178/ijiet.2022.12.10.1720
|View full text |Cite
|
Sign up to set email alerts
|

Examining University Students’ Attitude towards e-Learning and Their Academic Achievement during COVID-19

Abstract: Higher education around the world has moved to online teaching due to COVID-19 pandemic. Students in higher education are compelled to attend online classes and adopt e-learning mode. There is not much evidence on training the students to adopt e-learning and remote learning. However, do they have a positive attitude towards e-learning and has it affected their academic performance? Present study administered an e-learning attitude scale to 840 students of a reputed University to examine whether they have posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…On the other hand, this result is not similar to those of Uyar (2023), who found that male students, students with prior e-learning experience, access to the internet at home, personal computers, and students enrolled in technical courses exhibited more positive attitudes towards e-learning. Also, Prakasha et al (2022) showed that females had more positive attitudes toward e-learning than males, and males showed an avoidant elearning attitude. They also found that the results showed that socio-economic status did not influence students' e-learning attitudes.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…On the other hand, this result is not similar to those of Uyar (2023), who found that male students, students with prior e-learning experience, access to the internet at home, personal computers, and students enrolled in technical courses exhibited more positive attitudes towards e-learning. Also, Prakasha et al (2022) showed that females had more positive attitudes toward e-learning than males, and males showed an avoidant elearning attitude. They also found that the results showed that socio-economic status did not influence students' e-learning attitudes.…”
Section: Discussionmentioning
confidence: 96%
“…In this era of change in education, it is essential to understand students' attitudes toward e-learning. For example, students' attitudes toward e-learning can significantly impact their engagement, motivation, and, ultimately, their learning outcomes (Akcil & Bastas, 2020;Monib, 2023;Prakasha et al, 2022;Thapa et al, 2021;Uyar, 2023). E-learning is important by providing college students with flexible, accessible, and technology-enhanced learning experiences (Prevalla et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the key factor which contributes to the success of e-learning is e-learning readiness, without which even the best e-learning program can be a mere waste (Prakasha et al, 2022;Rohayani et al, 2015). Various studies have been conducted to determine the factors that could affect the readiness of the students towards e-learning.…”
Section: Introductionmentioning
confidence: 99%